The power of neuromarketing as a fuel to drive purchases in local retail (Piura 2024") - Becerra Rojas, Linda Diana (2024)
Neuromarketing studies the neurological brain responses to various marketing stimuli, such as visual, sound, colour and emotional elements, in order to understand in depth the cognitive and affective processes associated with consumer decision-making. Given its relevance, the objective is to determine how the power of neuromarketing acts as a fuel to drive purchase in a local retail store - Piura 2024. Methodologically, a quantitative approach was used with a non-experimental, descriptive-correlational and transversal design. A total of 384 frequent customers, of legal age and with purchasing power, participated. The findings of this study are an irrefutable testimony to the transformative power of neuromarketing in this local setting (Piura). With a Spearman correlation coefficient of 0.823 (p < 0.01), a strong and statistically significant positive correlation between neuromarketing and purchase decision is revealed, demonstrating that this innovative discipline has the ability to profoundly influence consumer behaviour. These results are a call to action for companies in the sector to adopt neuromarketing strategies that allow them to connect with their customers in a more effective and emotional way, thus unleashing an unprecedented impact on their commercial success.